(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This paper examines ways in which American ethnomusicologist and folklorist Alan Lomax (1915–2002), engaged with the Soviet Union during the Cold War through fieldwork, scholarly exchange, and international conferences. A passionate advocate for peacebuilding through culture and music, Lomax believed that shared artistic traditions could foster mutual understanding between nations. Best known for his recordings of folk music and his role in the American Blues and Folk revival movements, Lomax developed the Cantometrics system to analyze musical styles across cultures. His work emphasized “cultural equity”—the recognition and preservation of diverse musical traditions. Lomax visited the USSR for the first time in 1964 for the International Anthropological and Ethnological Congress in Moscow, and again between 1987 and 1989. He collaborated with Soviet ethnomusicologists such as Anna Rudneva and Emina Eldarova, and collected recordings from Tatar, Uzbek, Kazakh, Georgian, Azerbaijani and other ethnicities. His recordings and publications introduced American audiences to the rich musical traditions of non-Russian peoples of the USSR, encouraging appreciation of their diverse and beautiful cultures. Lomax’s work in the Soviet Union formed a key part of his broader vision of using music as a bridge across cultural and political divides. Using both the Alan Lomax and Emina Eldarova Archives, this paper gives an overview of his activities in the Soviet Union with an emphasis on his 1964 visit.